Shelf biogeochemical interactions and feedback processes in the Benguela upwelling system - Mashifane, Thulwaneng (Department of Oceanography, 2018)
Two coupled physical-biogeochemical models namely, (Regional Ocean Modelling System and Biogeochemical of Eastern Boundary Upwelling Systems) ROMS-BioEBUS (3D) and (Nucleus for European Modelling of the Ocean and Biogeochemical Flux Model) NEMO-BFM (1D) are applied in the Benguela upwelling system to understand biogeochemical interactions and their related feedback processes. The models are formulated differently but achieve similar objectives with respect to the physics and biogeochemistry. The BioEBUS model is used to simulate nitrogen processes under oxic and suboxic conditions in upwelling systems with no option for other cycles. Intermediary nitrogen processes, nitrous oxide production and nitrogen loss mechanisms are studied using this model. Physical and advection processes that drive the oceanic nitrogen cycle in the region are also studied with BioEBUS. The BFM is used to understand the implications of the nitrogen loss and suboxic-anoxic conditions on related biogeochemical cycles. The 1D model was selected for its low computational costs and flexibility for addition of new code. BFM includes the carbon, nitrogen, phosphorus, silicate, iron cycles and hydrogen sulphide production, which is a known occurrence in the Namibian shelf waters. New variables, nitrite and nitrous oxide production, are added in BFM to complete the nitrogen cycle. The nitrification process in BFM is also formulated in two stages as in BioEBUS to obtain comparative results in both models. Both models are compared and validated with data from the Maria S. Merian (MSM) 19/1b cruise and available products respectively. Simulated results from BioEBUS show primary and secondary nitrite maxima in the Benguela shelf waters. The primary nitrite maxima are attributed to nitrification and nitrate assimilation. Secondary nitrite maxima accumulate in the Angola-Benguela Front (ABF) oxygen minimum zone (OMZ) and are attributed to denitrification. Off Walvis Bay, these secondary nitrite maxima and ammonium are thought to be consumed by high rates of anaerobic ammonium oxidation (anammox). The nitrite maxima are restricted to the shelf off Walvis Bay and advected offshore in the ABF region. Interchanges between the poleward South Atlantic Central Water (SACW) and the equatorward, well-oxygenated Eastern South Atlantic Central Water (ESACW) drive the seasonality of nitrogen processes in the Benguela. Nitrous oxide concentrations are high in the ABF as a result of nitrification and accelerated production under suboxic conditions. Off Walvis Bay, nitrous oxide production is low when compared to the ABF. Nitrous oxide production in the ABF occurs in thermocline, intermediate and deeper water masses. Off Walvis Bay, nitrous oxide production in deeper water masses is missing because of the shallow coast. High fixed nitrogen fluxes in the Benguela are attributed to nitrification rather than anammox and denitrification. Simulated results show denitrification to be the dominant nitrogen loss mechanism in the Benguela shelf waters. Simulated results from BFM show higher nitrogen uptake rates than phosphate in shelf and offshore stations. The uptake rates are high on the shallow shelf due to luxury nutrient uptake. High N:P ratios occur at the stations at 21ᵒS than off Walvis Bay and are attributed to the presence of nutrient-rich, oxygen depleted SACW and denitrification respectively. Increased fixed nitrogen deficits (N*) occur in surface and subsurface waters at shallow stations as opposed to offshore. The positive N* anomalies off Walvis Bay are attributed to organic matter remineralization in deep, offshore stations. In contrast, increased phosphate (P*) concentrations occur in surface and subsurface waters. Phosphate is regenerated in subsurface waters and released under suboxic-anoxic conditions increasing P* concentrations. Nitrogen loss coupled with hydrogen sulphide production accelerate phosphate release in suboxic-anoxic bottom waters. The N:P stoichiometry, uptake rates, N* and P* concentrations appear to have considerable implications on potential estimated nitrogen fixation in the Benguela. BFM results suggest that the Benguela is a system characterized by excess nitrate in relation to silicate. This has been drawn from the low Si:N ratios observed at the simulated stations. A secondary Si:N peak is shown on the shallow coast due to high denitrification rates in suboxic waters. Note that high silicate concentrations occur in suboxic conditions and can be attributed to organic matter remineralization. The high silicate concentrations in the well-oxygenated offshore station are linked to sinking particles in deep waters. Increased silicate dissolution occurs in warm, surface waters and the particles that pass through the water column undissolved settle at the bottom where dissolution continues. From these results, it can be assumed that increased warming in the Benguela coastal waters should result in silicate being a limiting nutrient. This could affect carbon export as it has been shown that increased POC export is high in coastal waters due to ballasting of diatom biomass. The models used in this study simulated biogeochemical interactions in the Benguela fairly-well and can be applied in other regions.